Sepsis of appendicular origin: Revisión de la casuística del C. T.I. del Hospital de Clfnicas. - Peyroulou, Alfredo; di Leoni, Francisco; Correa, Humberto; Buroni, María; Bukstein, Jorge; Cuña, Ricardo (Cirugía del Uruguay, 1985)
22 cases of sepsis are analyzed retrospectively of appendicular origin, of patients treated in the C.T.I. Hospital de Clinicas between January 1973 and September 1983.